DEVELOPMENT AND VALIDATION OF DISPERSIVE LIQUID-LIQUID MICROEXTRACTION FOR THE DETERMINATION OF MULTICLASS PESTICIDE RESIDUES IN COMPLEX FOOD MATRIX - Khor, Livien; Chai, Mee Kin (Malaysian Journal of Science, 2014)
In this study, dispersive liquid-liquid microextraction (DLLME) which is known for its simplicity, rapidity and high recovery was developed coupling with gas chromatography-flame ionization detector (GC-FID) for the determination of pesticides of different chemical groups in tomato and cucumber samples. Parameters affecting the extraction efficiency of DLLME such as types and volume of extraction solvent and dispersive solvent, extraction time and ionic strength of aqueous solution were studied and optimized. Under the optimized conditions (0.8 mL acetone, dispersive solvent; 14.2 µL tetrachloroethylene, extraction solvent; 20 s extraction time; no salt addition), the relative recoveries of pesticides from tomato and cucumber samples at a dilution factor of 1:25 were in the range of 94.58 – 103.34% and 96.46 – 109.45% respectively. The limits of detections (LODs) of all pesticides except diuron from tomato and cucumber extracts were ranged from 7.5 – 15 µg/L and 15 – 39 µg/L respectively. All the LODs of pesticides except diuron extracted from both tomato and cucumber extracts using the proposed DLLME method coupled with GC-FID were still found to be lower than the maximum residue levels (MRLs) established by European Union and / or Codex Alimentarius. ABSTRAK Dalam kajian ini, pengekstrakan mikro cecair-cecair serakan (DLLME) yang terkenal dengan keringkasan, kepantasan dan pemulihan yang tinggi telah dibangunkan gandingan dengan gas kromatografipengesan pengionan api (GC-FID) untuk penentuan racun perosak beraneka kumpulan kimia dalam sampel tomato dan timun. Parameter yang mempengaruhi kecekapan pengekstrakan DLLME seperti jenis dan isipadu pelarut pengekstrakan dan pelarut penyebar, masa pengekstrakan serta kekuatan ionic larutan akueus dikaji dan dioptimumkan. Di bawah syarat-syarat yang optimum (0.8 mL aseton, pelarut penyebar; 14.2 µL tetrakloroetilena, pelarut pengekstrakan; 20 s masa pengekstrakan; tiada tambahan garam), relative pemulihan racun perosak daripada sampel tomato dan timun dengan factor pencairan 1:25 adalah dalam lingkungan 94.58 – 103.34% dan 96.46 – 109.45% masing-masing. Had pengesanan (LODs) bagi semua racun perosak yang diekstrak daripada tomato dan timun kecuali diuron dengan menggunakan kaedah DLLME bergandingan dengan GC-FID yang dicadangkan masih didapati lebih rendah daripada tahap maksimum sisa baki racun perosak yang ditetapkan oleh European Union dan/ atau Codex Alimentarius. Keywords: Dispersive liquid-liquid microextraction, gas chromatography-flame ionization detector, pesticides, tomato and cucumber extracts